“Gestión de riesgos ergonómicos en los puestos de trabajo del personal administrativo y docente en la Universidad Nacional de Chimborazo Campus Centro en la ciudad de Riobamba” - Quiroz Llangari, Dany Emerson (2017)
Ergonomic risk management is essential in any organization, especially if it is in higher education, where it is essential to foster a culture of security. Therefore, it should be an integral part of the activities and functions of the entity's staff, through the Management of ergonomic risks and the proposal of a manual of procedures. This research project aims at the management of ergonomic risks for the prevention of musculoskeletal disorders in the Administrative and Teaching areas of the National University of Chimborazo in its Campus Center, through the proposal of a manual of procedures; Which will reduce or mitigate the risk of personnel from occupational diseases from exposure to ergonomic risk factors. In order to achieve this objective, several methods of identification and evaluation of ergonomic risk factors were used: the RULA method, NIOSH method and CHECK LIST ISO 11228-3: 2007, as well as the collection of information and elaboration of Formats. Therefore, all the jobs in the aforementioned areas were analyzed, conducting personnel surveys, direct observation, recording of activities, use of software and setting up control measures according to the actual working conditions and personnel needs. The results in the Administrative and Teaching staff: from the RULA method a level of risk 2 was found; in the NIOSH method, when setting parameters for its application, the weight exceeds 3 kg, however, neither lifting nor depositing loads in standing position or With both hands, of the method CHECK LIST ISO 11228-3: 2007 the personnel complies with the conditions of intense use of finger / s, hand / so wrist / s and regular movements with some pauses or almost continuous movements within step 1 movements Repetitive / duration. The conclusion of the present project according to the RULA method the level of action was to possibly make some changes in the jobs and a more detailed evaluation, in the method NIOSH considers that in this case it is not necessary to continue with the evaluation, the CHECK method LIST ISO 11228-3: 2007 the mentioned conditions are not made more than 3h and there is no more than 1h without pause therefore no further evaluation is required. Thus proposing the manual of procedures for the prevention of musculoskeletal disorders derived from ergonomic risk factors.